Interlibrary loan practices handbook - Weible, Cherie L.; Janke, Karen L. (IG library, 2011)
In this new edition of the definitive Interlibrary Loan Practices Handbook, edited by CheriT Weible and Karen Janke, expert contributors clearly explain the complexities of getting materials for patrons from outside the library. This collection presents a complete view of the interlibrary loan (ILL) process, with contributions from all areas of the technical services community, providing. Guidance on how to do ILL efficiently and effectively, with advice on being a considerate borrower and lender. Details of preferred staffing and management techniques, showing how best practices can be implemented at any institution. Discussion of important issues that can fall between the cracks, such as hidden copyright issues, and the logistics of lending internationally. As consortia and other library partnerships share ever larger fractions of their collections, this book gives library staff the tools necessary for a smoothly functioning ILL system. --Book Jacket.